2018
DOI: 10.1186/s40635-018-0173-6
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary experience on the safety and tolerability of mechanical “insufflation-exsufflation” in subjects with artificial airway

Abstract: BackgroundCatheter suctioning of respiratory secretions in intubated subjects is limited to the proximal airway and associated with traumatic lesions to the mucosa and poor tolerance. “Mechanical insufflation-exsufflation” exerts positive pressure, followed by an abrupt drop to negative pressure. Potential advantages of this technique are aspiration of distal airway secretions, avoiding trauma, and improving tolerance.MethodsWe applied insufflation of 50 cmH2O for 3 s and exsufflation of − 45 cmH2O for 4 s in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 25 publications
0
25
2
1
Order By: Relevance
“…In this randomized cross-over trial, when inspiratory/expiratory pressures of 50 cmH 2 O were applied, lung compliance improved immediately after the intervention, and 10 minutes thereafter. Despite these encouraging previous results, other publications have consistently failed to nd bene ts (15,16,18). In our study, compliance of the respiratory system increased immediately after CPT + MI-E intervention.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…In this randomized cross-over trial, when inspiratory/expiratory pressures of 50 cmH 2 O were applied, lung compliance improved immediately after the intervention, and 10 minutes thereafter. Despite these encouraging previous results, other publications have consistently failed to nd bene ts (15,16,18). In our study, compliance of the respiratory system increased immediately after CPT + MI-E intervention.…”
Section: Discussioncontrasting
confidence: 78%
“…Nunes et al observed an improvement in SpO 2 after either endotracheal suctioning or MI-E (18), while other publications failed to corroborate these results (15,16). Sanchez-Garcia et al demonstrated an improvement in PaO 2 following MI-E (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently the safety of MI-E has been examined in endotracheally intubated patients. An observational study [120] reported no adverse events during MI-E use in these patients. The study authors concluded that MI-E may be safe and effective in the intubated population, but further work is required [120].…”
Section: Take-home Messagesmentioning
confidence: 78%
“…Only 2 papers in the literature report pressures of 50 cm H 2 O: Sánchez-García et al, 11 who applied insufflation of 50 cm H 2 O and exsufflation of Ϫ45 cm H 2 O in subjects with an endotracheal tube or tracheostomy cannula; and Guerin et al, 10 who used this setting of MI-E in a bench study performed on a lung model with different sizes of endotracheal and tracheostomy tubes. Both studies considered the presence of endotracheal and tracheostomy tubes, which are known to offer high air-flow resistances that therefore require higher pressures.…”
Section: Effects Of Mechanical Insufflation-exsufflation On the Breatmentioning
confidence: 99%